2020
DOI: 10.1021/acs.jafc.0c03907
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibited Endothelial Dysfunction and Atherosclerosis in Apolipoprotein E-Deficient Mice: Critical Roles for NADPH Oxidase and Heme Oxygenase-1

Abstract: NADPH oxidase-dependent superoxide (O 2 •− ) production and oxidative stress play important roles in endothelial dysfunction and atherosclerosis. Herein, we investigated the potential effects of dietary quercetin, a flavonoid derived in the diet from vegetables and fruit, on vascular endothelial function and atherosclerosis in the high-fat diet (HFD)-fed apolipoprotein E-deficient (ApoE −/− ) mice. Dietary quercetin treatment significantly suppressed endothelial dysfunction and aortic atherosclerosis in HFD-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 44 publications
(211 reference statements)
3
38
0
Order By: Relevance
“…In this study, quercetin could inhibit LPS-induced attachment of monocytes to HUVECs by downregulating expressions of VCAM-1 and ICAM-1 in vitro as well as suppress the expression of pro-inflammatory cytokines, which demonstrated the ability of quercetin to ameliorate endothelial dysfunction. Coincident with our results, quercetin was reported to remarkably suppress endothelial dysfunction and significantly attenuate atherosclerotic lesion progression in high-fat diet (HFD)-fed ApoE −/− mice (23). Likewise, it was demonstrated that quercetin had an inhibitory action on the expression of proinflammatory cytokines in hypercholesterolemic diet (HCD)-fed rats (24).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, quercetin could inhibit LPS-induced attachment of monocytes to HUVECs by downregulating expressions of VCAM-1 and ICAM-1 in vitro as well as suppress the expression of pro-inflammatory cytokines, which demonstrated the ability of quercetin to ameliorate endothelial dysfunction. Coincident with our results, quercetin was reported to remarkably suppress endothelial dysfunction and significantly attenuate atherosclerotic lesion progression in high-fat diet (HFD)-fed ApoE −/− mice (23). Likewise, it was demonstrated that quercetin had an inhibitory action on the expression of proinflammatory cytokines in hypercholesterolemic diet (HCD)-fed rats (24).…”
Section: Discussionsupporting
confidence: 83%
“… 62 Furthermore, a recent study conducted by Mengjuan et al, 2020 exhibited that quercetin significantly suppressed endothelial dysfunctioning and atherosclerotic plaque by attenuating the expression of p47phox and NADPH related oxidative damage attributed vital contribution of flavonoids in vascular diseases. 63 However, a double-blind randomized clinical trial has demonstrated the profound effect of quercetin on systolic blood pressure, but non-significant activity was analyzed on diastolic blood pressure and inflammatory cytokines. Thus, in vitro biological effects of quercetin are not proven in human studies and need to be elucidated further on different doses to obtain the better outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent review articles by Patel et al ( 39 ) and Deng et al ( 40 ) emphasize the protective role of quercetin in endothelial dysfunction from oxidative stress and its potential use as an antiatherosclerotic agent and in CVD prevention. Quercetin prevents endothelial dysfunction by competitively inhibiting myeloperoxidase-dependent HOCl generation and NADPH oxidase-dependent O 2 · – production that play a crucial role in atherosclerosis ( 41 , 42 ). Thus, our results are in line with the current evidence of using natural phytochemicals as a complementary remedy and in CVD prevention.…”
Section: Discussionmentioning
confidence: 99%